A guideline for employing PSIM on power converter applications: Prototyping and educational tool - Alonso, A. M.S. [UNESP] (2018)
Fast prototyping tools for power electronics and control systems are becoming handful players on effortlessly translating computer simulated results into real experimental validations, not abdicating reliability. Among many alternatives, PSIM distinguishes itself from other platforms by providing fixed-step time simulations and quick access to DSP programming. This work aims at showing a starting point for the interaction with the PSIM SimCoder module, and how to take advantage of its features to specifically develop codes employed on power converter applications and for educational purposes. The off-the-shelf TMS320F28335 Experimenter Kit is commonly chosen as target. Example cases accompanied by experimental results are provided for the implementation of an IIR filter, a PLL algorithm, and the generation of three-level PWM signal for single-phase converters. Yet, some discussions regarding the constraints of such tool are pointed out.